2017
DOI: 10.1002/jrs.5115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphorus compounds in soils by deep ultraviolet (DUV) Raman microspectroscopy

Abstract: Deep ultraviolet Raman microspectroscopy was successfully investigated as a new approach to analyze the chemical state of phosphorus compounds directly in soil. We demonstrate that ultraviolet excitation has the advantage to avoid the interference with the strong fluorescence, which occurs in the visible spectral range caused by organic matter in soils. Furthermore, the spatial resolution of <1 μm2 enables the detection of very small phosphorus particles. For some organic phosphorus compounds (β‐glycerophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This observation is in accordance with the literature where a coincidence between organic matter and calcite has been reported for certain soil types. 22 In the next step, using multivariate analysis, the SERDS spectra will be correlated with the SOM and nitrogen contents as determined by laboratory reference analyses to assess whether the spectroscopic data can be used to determine these key soil parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is in accordance with the literature where a coincidence between organic matter and calcite has been reported for certain soil types. 22 In the next step, using multivariate analysis, the SERDS spectra will be correlated with the SOM and nitrogen contents as determined by laboratory reference analyses to assess whether the spectroscopic data can be used to determine these key soil parameters.…”
Section: Resultsmentioning
confidence: 99%
“…A serious drawback of this excitation with high-energetic laser photons is the radiation-induced damage of specimens that has been reported, particularly for organic compounds. 22 Shifted excitation Raman difference spectroscopy (SERDS) 23,24 is a powerful physical approach to separate the characteristic molecular fingerprint from interfering contributions. The basic principle behind SERDS is that the sample is consecutively excited at two slightly different excitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vogel et al have characterized phosphorus compounds in soils by deep ultraviolet Raman microspectroscopy. They demonstrated that UV excitation has the advantage of avoiding strong fluorescence, which occurs in the visible range caused by organic matter in soils . Xia et al described a SERS optical fiber probe with plasmonic end‐facet.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…They demonstrated that UV excitation has the advantage of avoiding strong fluorescence, which occurs in the visible range caused by organic matter in soils. [229] Xia et al described a SERS optical fiber probe with plasmonic end-facet. To further enhance the SERS enhancement factor, a hybrid graphene/Au nanotriangle structure is transferred onto the end-facet of the fiber probe to enable SERS.…”
Section: New or Emerging Techniquesmentioning
confidence: 99%